Modelling and transient response study of hydraulic servo actuator. Issue 1 (August 2021) - Ibrahim, E E; Elnady, T; Saleh, I; Hassan, S
Abstract: This paper presents a mathematical model of electro hydraulic servo system (EHS) using two-stage electrohydraulic servovalve (EHSV), by the aim of Matlab-simulink-simscape multibody to predict the flow characteristics (pressure/flow rate) with changing the parametric configuration of (EHSV), these parameters could be used to estimate the error at different operating conditions. It includes establishing mathematical model, controller model and validating the performance of the (EHSV) by experimental result of published work using the data of servovalve labelled B.31.210.12.1000.U2V (mechanical feedback) manufactured by PPT - Trstenik. The effect of changing servovalve orifice diameter (0.25, 0.30, and 0.35) mm, show that increasing the orifice diameter of the servovalve leads to increase the transient time but decrease the system overshoot. The pressure behaviour is plotted and shows that increasing the orifice diameter leads to increasing the pressure inside the system as to reach the relieve pressure.